Emulgel preparation from ethanol extract of red ginger rich in 6-shogaol as therapy for diabetic neuropathy pain: targeting TRPV-1 down-style - Fifteen Aprila Fajrin; Diana Holidah; Fransiska Maria Christianty; Ika Puspita Dewi; Arief Nurrochmad; Heni Nurhidayah (Journal of Basic and Clinical Physiology and Pharmacology, 2026)
Abstract Objectives Painful diabetic neuropathy is a long-term complication of diabetes mellitus. However, the limitations of topical drug therapies have led to the development of plant-based treatments, such as red ginger. This study aimed to investigate the effectiveness of a red ginger extract emulgel (RGEE) for PDN. Methods Mice were divided into seven groups: normal, PDN, positive control using capsaicin cream, and four treatment RGEE at 1 %, 2%, 3%, and 4 %. Mice were induced diabetic using streptozotocin 120 mg/kg BW. On the 14th day, topical treatments were administered for 28 days, with weekly monitoring of hyperalgesia. Mice were sacrificed on the 42nd day, and the plantars were collected. Results The 3 % RGEE had the most effective activity in reducing hyperalgesia, as well as the number of neutrophils and lymphocytes. In addition, the 3 % RGEE reduced the expression of TRPV1 in the plantar of PDN mice and proved to be safe through acute dermal toxicity. Conclusions Red ginger extract emulgel 3 % effectively reduced hyperalgesia, inflammation, and TRPV1 expression and was proven to be safe.